Analysis of Learning Natural Sciences through 2013 Curriculum-Based Textbooks with KTSP Patterns in Elementary Schools: Case Study at PTQ Annida Elementary School, Salatiga City. - Yanti, Sevi (Science Education and Application Journal, 2023)
Choosing book sources as teaching materials, it is important to determine before the teacher conducts the learning process so that students do not experience misconceptions about understanding Natural Sciences from the start. This type of research is a qualitative research with a descriptive approach. While the data sources in this study were obtained from observations in the form of learning process activities and the results of interviews with third grade teachers. The supporting data is good from the Learning Implementation Plan (RPP). Student and teacher handbooks, syllabus, and teacher notes. The purpose of the study was to find out science learning through the 2013 curriculum text book with the KTSP pattern, namely the ESPS book published by Erlangga class III. In the book, it can be seen from the concept of presenting science material which is made simple, modern and makes it easier for students to master basic competencies in science learning, so that it can be applied to everyday life. The ESPS textbook published by Erlangga has referred to the 2013 curriculum in the form of subject presentations not in the form of thematic learning. Based on the analysis of the entire chapter, the 2013 curriculum text book with KTSP pattern produces a complete understanding of science concepts, fosters students' critical thinking, encourages students to be able to solve problems that exist in everyday life.